Managing fruit rot diseases of Vaccinium corymbosum - Neugebauer, Kerri A.; Mattupalli, Chakradhar; Hu, Mengjun; Oliver, Jonathan E.; VanderWeide, Joshua; Lu, Yuzhen; Sullivan, Kevin; Stockwell, Virginia O.; Oudemans, Peter; Miles, Timothy D. (Frontiers in Plant Science, 2024)
Blueberry is an important perennial fruit crop with expanding consumption and production worldwide. Consumer demand for blueberries has grown due to the desirable flavor and numerous health benefits, and fresh market production in the U.S. has risen in turn. U.S. imports have also increased to satisfy year-round consumer demand for fresh blueberries. Preand post-harvest fruit diseases such as anthracnose (caused by Colletotrichum spp.) and botrytis fruit rot (caused by Botrytis spp.) have a significant impact on fruit quality and consumer acceptance. These are also among the most difficult diseases to control in the blueberry cropping system. These latent pathogens can cause significant losses both in the field, and especially during transport and marketplace storage. Although both diseases result in rotted fruit, the biology and infection strategies of the causal pathogens are very different, and the management strategies differ. Innovations for management, such as improved molecular detection assays for fungicide resistance, postharvest imaging, breeding resistant cultivars, and biopesticides have been developed for improved fruit quality. Development and integration of new strategies is critical for the long-term success of the blueberry industry.